2001
DOI: 10.5358/hsj.20.105
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of Geoemydine Turtles (Reptilia: Bataguridae).

Abstract: Abstract:Monophyly of the batagurid subfamily Geoemydinae was evaluated, and phylogenetic relationships within the subfamily were inferred on the basis of 35 morphological characters. Two approaches, parsimony analysis using the branch and bound algorithm, and neighbor joining clustering of an absolute distance matrix, were used. The results of these analyses yielded phylograms that were almost identical in branching topology, and poorly supported the monophyly of Geoemydinae. This subfamily thus seems to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 26 publications
6
64
0
1
Order By: Relevance
“…Of these, however, yuwonoi was reassigned to a new monotypic genus, Leucocephalon, and depressa was allocated to Heosemys on the basis of a molecular phylogenetic analysis by McCord et al (2000). Yasukawa et al (2001), based on a cladistic analysis of morphological data for representatives of almost all geoemydid genera recognized to date, confirmed the relationships "(spengleri, japonica) silvatica", but retained the phylogenetic status of leytensis as unresolved. In their comprehensive molecular phylogenetic analysis of the family Geoemydidae, Spinks et al (2004) demonstrated the sister-group relationship of Geoemyda (as represented by spengleri and japonica) with the genus Siebenrockiella (as represented by crassicollis).…”
Section: 2mentioning
confidence: 94%
“…Of these, however, yuwonoi was reassigned to a new monotypic genus, Leucocephalon, and depressa was allocated to Heosemys on the basis of a molecular phylogenetic analysis by McCord et al (2000). Yasukawa et al (2001), based on a cladistic analysis of morphological data for representatives of almost all geoemydid genera recognized to date, confirmed the relationships "(spengleri, japonica) silvatica", but retained the phylogenetic status of leytensis as unresolved. In their comprehensive molecular phylogenetic analysis of the family Geoemydidae, Spinks et al (2004) demonstrated the sister-group relationship of Geoemyda (as represented by spengleri and japonica) with the genus Siebenrockiella (as represented by crassicollis).…”
Section: 2mentioning
confidence: 94%
“…In the present study, Cuora, Cyclemys, and Pyxidea were classified into the Cyclemys group, which was derived from a Heosemys-like ancestor, and the 4 genera were united into a Heosemys complex (Bramble, 1974). Afterwards, the Cuora were divided into Cuora and Cistoclemmys based on turtle morphology and 4 chromosomal characteristics (Hirayama, 1984;Yasukawa et al, 2001). However, Honda (2002) recommended synonymizing Cistoclemmys and Pyxidea with Cuora based on a phylogenetic analysis of rRNA sequences from mtDNA (Honda et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, no synapomorphic morphological character states are known for the two clades (e.g., Honda et al 2002;Hirayama et al 2007). Actually, because Ocadia differs much from Chinemys and Mauremys in several skull and shell characters (e.g., McDowell 1964;Gaffney and Meylan 1988;Yasukawa et al 2001), we retain the genus Ocadia for disclosing its past species diversity from paleontological view in the present study. Type locality.…”
Section: Systematicsmentioning
confidence: 99%
“…MTE1 is similar to Chinemys, Cuvierichelys, Mauremys, Ocadia, Palaeochelys, Sacalia, and Siebenrockiella in lacking the plastral hinge and in having the entoplastron intersected by the humero-pectoral sulcus and the neurals short-sided anteriorly. In addition, MTE1 has four informative character states for genus level taxonomy (Table 1): (1) second and third vertebrals nearly rectangular, as long as wide (modified from Hirayama et al 2007), (2) absence of serration on the posterior margin of the carapace (e.g., Ernst and Barbour 1989;Yasukawa et al 2001), (3) medial length of the gular shorter than the interhumeral sulcus , and (4) the plastral buttresses moderately developed, extending to half way of the costals . Of these, the character (3) and (4) are known as diagnostic characters for the genus Ocadia ), but variably seen in several comparative taxa ( (2) is informative for discriminating Ocadia from several species of Mauremys as well as a few Palaeochelys (P. laurenti), and Siebenrockiella (Sacco 1889;Ernst and Barbour 1989;Claude et al 2007;Chesi et al 2009).…”
Section: Ocadia Tanegashimensismentioning
confidence: 99%